Pengaruh Penggunaan Teknik Membaca Cepat Pada Mata Pelajaran Bahasa Indonesia Kelas VII MTs NW Teros Tahun Pelajaran 2018/2019 - Fathurrahman, Fathurrahman (khatulistiwa, 2020)
This study aims to determine the increasing effect of using speed reading techniques on Indonesian subjects on class VII MTs NW Teros in the 2018/2019 academic year. This research was conducted in MTs. NW Teros, Teros Village, Labuhan Haji District, East Lombok. This study uses a quantitative approach. The population of this study was 49 students of class VII. Data collection techniques were carried out through test and observation methods. Data analysis was carried out by statistical t-test (t-test). The results showed that from the calculation results above, it turns out that the "t" value obtained in this study is 0.61, while the "t" value in the normal curve table with a test level of 5%, 95% truth level = 0.95. To be able to use the normal curve table, then 0.95: 2 = 0.475, the normal curve table shows the number 1.96. Based on this fact, the "t" value obtained in this study is below the number of rejections of the null hypothesis. This means that this research is non-significant, where the null hypothesis is accepted and the alternative hypothesis is rejected. The conclusion of the study is that there is no effect of using speed reading techniques on Indonesian class VII MTs subjects. NW Wins 2018/2019 Academic Year.